We are displaced: My journey and stories from refugee girls around the world - Yousafzai, Malala; Welch, Liz (London Weidenfeld & Nicolson, 2019)
Nobel Peace Prize winner and bestselling author Malala Yousafzai introduces some of the faces behind the statistics and news stories we read or hear every day about the millions of people displaced worldwide.Malala's experiences visiting refugee camps caused her to reconsider her own displacement - first as an Internally Displaced Person when she was a young child in Pakistan, and then as an international activist who could travel anywhere in the world, except to the home she loved. In We Are Displaced, which is part memoir, part communal storytelling, Malala not only explores her own story of adjusting to a new life while longing for home, but she also shares the personal stories of some of the incredible girls she has met on her various journeys - girls who have lost their community, relatives, and often the only world they've ever known. In a time of immigration crises, war and border conflicts, We Are Displaced is an important reminder from one of the world's most prominent young activists that every single one of the 68.5 million currently displaced is a person - often a young person - with hopes and dreams, and that everyone deserves universal human rights and a safe home.
Keywords: Nobel Peace Prize Winner; Experiences of Young Refugees; Global Activist